2010
DOI: 10.1002/cctc.201000083
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Morphology, Magnetic and Optical Properties of Li‐Doped MgO

Abstract: Li-doped MgO is a potential catalyst for the oxidative coupling of methane, whereby surface Li+ O- centers are suggested to be the chemically active species. To elucidate the role of Li in the MgO matrix, two model systems are prepared and their morphological, optical and magnetic properties as a function of Li doping are investigated. The first is an MgO film deposited on Mo(001) and doped with various amounts of Li, whereas the second is a powder sample fabricated by calcination of Li and Mg precursors in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 106 publications
(140 citation statements)
references
References 55 publications
7
124
0
7
Order By: Relevance
“…Both on a Li-doped MgO film grown on a Mo(001) substrate but also on Li-doped MgO powders surface segregation of Li was observed above 700 K and Li-desorption above 1,050 K. Figure 9 shows the surface of such a Li-doped MgO-film upon heating to 700 and 1,050 K. The formation of Li-rich surface oxides patches and the rectangular surface defects left behind upon Lidesorption are clearly seen and in line with ab-intio thermodynamic calculations [67]. It can be summarized that Li- [67] doping leads to a pronounced morphology change and defect formation on the MgO surface which has a positive effect on the OCM activity. However, the initially high OCM activity cannot be sustained due to Li-losses under reaction conditions rendering Li/MgO and also other Li-based OCM catalysts unusable for process development.…”
Section: Ocm With Dioxygensupporting
confidence: 74%
See 1 more Smart Citation
“…Both on a Li-doped MgO film grown on a Mo(001) substrate but also on Li-doped MgO powders surface segregation of Li was observed above 700 K and Li-desorption above 1,050 K. Figure 9 shows the surface of such a Li-doped MgO-film upon heating to 700 and 1,050 K. The formation of Li-rich surface oxides patches and the rectangular surface defects left behind upon Lidesorption are clearly seen and in line with ab-intio thermodynamic calculations [67]. It can be summarized that Li- [67] doping leads to a pronounced morphology change and defect formation on the MgO surface which has a positive effect on the OCM activity. However, the initially high OCM activity cannot be sustained due to Li-losses under reaction conditions rendering Li/MgO and also other Li-based OCM catalysts unusable for process development.…”
Section: Ocm With Dioxygensupporting
confidence: 74%
“…Li/ MgO was reviewed [66] and studied again in great detail but neither experiment nor theory gave evidence that Li þ O À exists under OCM conditions [67]. Both on a Li-doped MgO film grown on a Mo(001) substrate but also on Li-doped MgO powders surface segregation of Li was observed above 700 K and Li-desorption above 1,050 K. Figure 9 shows the surface of such a Li-doped MgO-film upon heating to 700 and 1,050 K. The formation of Li-rich surface oxides patches and the rectangular surface defects left behind upon Lidesorption are clearly seen and in line with ab-intio thermodynamic calculations [67]. It can be summarized that Li- [67] doping leads to a pronounced morphology change and defect formation on the MgO surface which has a positive effect on the OCM activity.…”
Section: Ocm With Dioxygenmentioning
confidence: 99%
“…MgO films with small Li amounts incorporated into the bulk layers still exhibit the rocksalt lattice of the bare oxide [2]. However, the film crystallinity is reduced, i.e., oxide terraces are smaller and defect lines are less straight than in the nondoped case [ Fig.…”
Section: A Experimental Resultsmentioning
confidence: 99%
“…It was further assumed that electron transfer from methane into these low-lying hole states triggers the abstraction of a H atom from the adsorbate as the initial step for subsequent coupling reactions of the remaining CH 3 units to longer hydrocarbons [1]. Although put forward long ago, this mechanism for the oxidative coupling of methane still poses a number of questions, both from the experimental and theoretical viewpoints [2][3][4]. Based on a review of experimental and theoretical studies, Arndt et al demonstrated that the suggested reaction pathway cannot be a dominating one [3].…”
Section: Introductionmentioning
confidence: 99%
“…Here thin film models proved crucial as they were providing evidence about the role of Li-dopants for restructuring MgO which features more steps and corners [29]. Gas phase clusters are useful model systems for catalysis if they feature the same active site as solid catalysts, enzymes or molecular catalysts.…”
Section: Introductionmentioning
confidence: 99%